2003
DOI: 10.1007/s00535-003-1207-7
|View full text |Cite
|
Sign up to set email alerts
|

Folic acid, polymorphism of methyl-group metabolism genes, and DNA methylation in relation to GI carcinogenesis

Abstract: DNA methylation is the main epigenetic modification after replication in humans. DNA (cytosine-5)-methyltransferase (DNMT) catalyzes the transfer of a methyl group from S-adenosyl-L-methionine (SAM) to C5 of cytosine within CpG dinucleotide sequences in the genomic DNA of higher eukaryotes. There is considerable evidence that aberrant DNA methylation plays an integral role in carcinogenesis. Folic acid or folate is crucial for normal DNA synthesis and can regulate DNA methylation, and through this, it affects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
50
0
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(52 citation statements)
references
References 70 publications
1
50
0
1
Order By: Relevance
“…It has been shown that a deficiency of this nutrient results in DNA hypomethylation. The role of folate and the above germ-line variants in relation to cancer has been reviewed (16,17).…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that a deficiency of this nutrient results in DNA hypomethylation. The role of folate and the above germ-line variants in relation to cancer has been reviewed (16,17).…”
Section: Introductionmentioning
confidence: 99%
“…It facilitates the conversion of 5, 10-methylene THF to 5-methyl THF, and leads point mutations and/or chromosomal breaks. Also, it may cause decline of 5-methyl THF to induce a decrease of the conversion of homocysteine to methionine, which could result in a carcinogenesis process of DNA hypomethylation (Stern et al, 2000;Fang and Xiao, 2003;Blount et al, 2007). Approximately 60 polymorphisms have been described in the MTHFR gene (Leclerc and Rozen, 2007).…”
mentioning
confidence: 99%
“…blood pressure, hyperglycemia (Brasacchio et al, 2009);(El-Osta et al, 2008); ischemia (Kumral et al, 2009;Parker et al, 2008)) and/or diet (e.g. butyrate (Vidali et al, 1978), organosulfur (Tissenbaum & Guarente, 2001), dietary polyphenols (Howitz et al, 2003), folate, and choline (Fang & Xiao, 2003)) may induce adaptive or compensatory epigenetic modifications within the placental and/or fetal genomes. Thus, periconceptional and early pregnancy events may affect the placental and/or fetal epigenome.…”
Section: Complications Of Pregnancymentioning
confidence: 99%